The Effects of Grammar Mastery and Vocabulary Mastery Towards Students Argumentative Writing - Woro Hestiningsih (Deiksis, 2016)
The aim of the research is to obtain the empirical data and analyze the effects of grammar mastery and vocabulary mastery towards students’ argumentative writing. Research method is survey with multiple correlation technique. This research was conducted at privates senior high schools in Cibinong, in school year 2011-2012. Collecting data was done by using two kinds of instruments, multiple choice and essay writing. Multiple choice tests are used to measure the grammar mastery and vocabulary mastery of the students’. Essay writing is used to assess the argumentative writing especially analytical exposition. It shows that there are effects of grammar mastery and vocabulary mastery towards students’ argumentative writing.Key Words: Grammar Mastery, Vocabulary Mastery, and Students Argumentative Writing.